Enhancing Knowledge and Attitudes Regarding Anemia Among Adolescent Girls Through Multidisciplinary Education: A One-Group Pretest–Posttest Study in Central Sulawesi - Taqwin, Taqwin; Linda, Linda; Sakti, Putri Mulia; Pani, Widya; Pont, Anna Veronica; Lisnawati, Lisnawati (Journal of Health and Nutrition Research, 2025)
Anemia in adolescent girls is a serious public health problem, especially in developing countries. Teenage girls are prone to anemia due to rapid growth, menstruation, and low iron intake. This study aims to evaluate the effectiveness of comprehensive education in improving adolescents' knowledge and attitudes towards anemia, consumption of blood-boosting tablets, and anemia-preventing diet. The study used a pre-experimental design with a one-group pretest-posttest approach. Forty-one students aged 14-18 from Banawa Tengah I Public Senior High School, Donggala were selected using the quota method. A multidisciplinary team delivered educational interventions, including materials on anemia, blood-boosting tablets, and anemia diets. The measurement of knowledge and attitudes was carried out using questionnaires tested for validity and reliability. Data analysis used the Wilcoxon signed-rank test. The results showed an increase in the knowledge score from 6.46 to 7.90 and the attitude score from 47.32 to 49.37. Both variables had statistically significant differences (ρ < 0.001 for knowledge and ρ = 0.008 for attitude). In conclusion, direct and comprehensive education effectively increases adolescent girls' knowledge and attitudes about anemia prevention. Similar programs are recommended to be integrated into school health activities and supported by the role of families and communities